User-Generated Content or Influencer Marketing: Which Has a Greater Impact on Customer Trust on TikTok? - Wijaya, Florencia; Putri, Liestyaningrum Rahmadhani Wisnu (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to compare the influence of User Generated Content (UGC) and Influencer Marketing on customer trust on the social media platform TikTok. TikTok has evolved into one of the most popular digital marketing platforms, supported by an algorithm that enables viral and interactive content dissemination. UGC refers to content created by users based on personal experiences, while Influencer Marketing involves public figures with a wide audience and strong influence. This research employs a quantitative approach with a causal-comparative method. The sample consisted of 200 respondents who are active TikTok users. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that both UGC and Influencer Marketing have a positive and significant effect on customer trust. However, Influencer Marketing exerts a more dominant influence, as indicated by a higher beta coefficient value. The model explains 59% of the variation in customer trust. These findings indicate that Influencer Marketing is more effective in building customer trust compared to UGC, although both strategies are complementary. Therefore, marketers are advised to strategically combine both approaches to enhance positive customer perception and brand loyalty on TikTok.